Good Corporate Governance Sebagai Wujud Peran Dewan Pengawas Syariah Di Perbankan Syariah - Afni Amelia; Fifi Hayrani Siregar; Putri Balqis; Wilda Sri Munawaroh; Ova Novi Irama (INTERNATIONAL, Journal of Sharia Business Management, 2024)
The operation of this sharia bank cannot be separated from the demands of implementing good corporate governance (Good Corporate Governance) hereinafter referred to as GCG. This research uses a type of literature study or literature review with data collection methods using two approaches, namely library research and internet searches. The literature that is the focus of this research are journals and articles that are directly related to Good Corporate Governance (GCG). In the process of searching on the internet, researchers can use various methods such as searching, browsing, or downloading to obtain the information needed according to the research objectives. The databases used when searching for research journals are Google Scholar, Sciencedirect, and Researchgate. The Sharia Supervisory Board (DPS) is tasked with supervising banking operations and sharia banking products according to Sharia principles. DPS must ensure that GCG principles are implemented in all aspects and at all levels of the company. Through the effective implementation of sharia GCG, sharia banking not only gains public trust, but also builds a solid foundation for the growth of the sharia financial industry by combining ethical and balanced financial values.